Systematic Literature Review: Analysis of Determinants of The Quality of BRT Transportation using The Kaizen Method - Haryadi Sarjono; Yuliana Tri Wulandari (International Journal of Organizational Business Excellence, 2022)
Transportation comes from the Latin word tranportare, and has 2 utilities, namely place utility and time utility to facilitate relationships between other communities. Article searches are carried out using the "Google Scholar" and "ResearchGate" databases. The preparation of the research follows the basic steps of research which include determining the research objectives, conducting a literature review on the development of the Kaizen method. This paper finds that the kaizen method has been used in various social fields, transportation and so on. Road transport is a major contributor to C02 emissions due to dependence on fossil fuels. The main causes of emissions are motor vehicles, buses, taxis, and intercity foam. The main reference for the design and development of Transjakarta is the BRT system. Transjakarta is considered as one of the cities in the world that has failed to achieve high quality BT services. Building a sustainable transportation system for big cities and complexes is not an easy thing. The Transjakarta BRT system is projected to be a sustainable solution for the ever-increasing needs of urban transportation. Various problems and shortcomings are interconnected such as: Inefficiency (low carrying capacity), physical problems (design) and construction), operational issues of mismanagement and political issues of lack of transparency and corruption. Refers to the best practice of the BRT system in the world, development of regulations and plans have been studied and implemented extensively.